HARASSMENT, WORKERS' MENTAL HEALTH AND THE POTENTIAL OF ILO CONVENTION NO. 190: AN ANALYSIS BASED ON THE FRANCE TÉLÉCOM CASE - de Almeida, Victor Hugo [UNESP]; Scodro, Catharina Lopes; Tristão, Ana Clara [UNESP] (RGSA- Revista de Gestao Social e Ambiental, 2024)
Objective: In the process of being privatized, France Télécom implemented the NExT and Act plans, containing a series of internal policies aimed at reducing jobs, causing suffering to workers. Upon analysing the case, the French Judiciary observed the occurrence of the crimes of institutional moral harassment, condemning both the company and the individuals responsible for its management. The objective of this study is to examine the influence of organizational aspects on the balance of the work environment and on the workers' mental health, in light of the France Télécom case and the theory of the labour-environmental perspective. Method: The methodology adopted for this research comprises the bibliographic research technique, the documentary method, and the case method, as methods of procedure; and the inductive method, as a method of approach. Results and Discussion: A close relationship is observed between labour-environmental organizational aspects and harassment in the work context, influencing the balance in the work environment and workers' health. Research Implications: This study highlights the importance of regulations such as ILO Convention No. 190 to enhance the protection of workers' mental health, suggesting organizational changes that prioritize well-being in the work environment. Originality/Value: This study contributes to the field of labour studies by integrating legal and psychosocial analysis, demonstrating the significance of organizational policies in the development and maintenance of workers' mental health.
Keywords: Convention No. 190; ILO; institutional harassment; labour-environmental balance; moral harassment